Cертифицированный учитель в образовательном пространстве школы как фактор достижения нового качества - Абильдинова, Ж.И. (My University, 2016)
Relevance. The words of President NursultanNazarbayev that "the result of student’s learning should be mastering of critical thinking skills, self-searching and deep searching of information", define the vector of action in the field of education. Questions of updating the content of education, defined in the State Compulsory Standards of Primary Education (SCSPE), approbation of which begins with 2015-2016 academic year, focus attention of teaching community on the results of modern education, expressed in the form of skills and abilities that require a different approach to the organization of teaching and educational process. Modernization of the professional development of pedagogical workers has contributed to the professional growth of teachers for the achievement of tasks assigned by the President. Goal. Determine the impact of activities of certified teachers at the results of quality of knowledge of the educational process. Methods. Conversation, theoretical analysis, generalization. Result. 1. Growth of the quality of students' knowledge in the II quarter in comparison with the I quarter of 2015-2016 school year, is 3.5%; 2. The positive dynamics of growth Olympiads’ medalists, the Scientific Society of Students (SSS), intellectual games; 3. The presence of a creative learning environment, enabling creative self-realization of educational process for students and teachers. Conclusion. As a result of certified teachers’ activity increases the quality of teaching and learning. Teachers are actively exploring methods of organization of students’ reflection in the classroom and self- reflection in their own teaching practice.
Keywords: a certified teacher; level courses; the practice of teaching and learning